2018
DOI: 10.1111/acel.12814
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of mitochondrial DNA deletions is a private mechanism of aging in long‐lived animals

Abstract: Disruption of mitochondrial metabolism and loss of mitochondrial DNA (mtDNA) integrity are widely considered as evolutionarily conserved (public) mechanisms of aging (López‐Otín et al., Cell, 153, 2013 and 1194). Human aging is associated with loss in skeletal muscle mass and function (Sarcopenia), contributing significantly to morbidity and mortality. Muscle aging is associated with loss of mtDNA integrity. In humans, clonally expanded mtDNA deletions colocalize with sites of fiber breakage and atrophy in ske… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Further downstream sources of mitochondrial heterogeneity, such as translation errors, have also been shown to have physiological consequences in budding yeast (Suhm et al, 2018). The age-related functional decline of mitochondria in shorter-lived animals (Itsara et al, 2014; Brandt et al, 2017) might not be explained directly by mtDNA mutations (Vermulst et al, 2007; Lakshmanan et al, 2018) (see also recent, contrasting, results in Drosophila ; Kauppila T.E. et al, 2018; Samstag et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further downstream sources of mitochondrial heterogeneity, such as translation errors, have also been shown to have physiological consequences in budding yeast (Suhm et al, 2018). The age-related functional decline of mitochondria in shorter-lived animals (Itsara et al, 2014; Brandt et al, 2017) might not be explained directly by mtDNA mutations (Vermulst et al, 2007; Lakshmanan et al, 2018) (see also recent, contrasting, results in Drosophila ; Kauppila T.E. et al, 2018; Samstag et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion mutations have been associated with local fiber atrophy and breakage in mice (Wanagat et al, 2001; Khrapko and Vijg, 2009) and rhesus monkeys (Aiken et al, 2002) (although the causative role of mtDNA mutations in aging for shorter-lived animals is contested; Vermulst et al, 2007; Kauppila T.E. et al, 2018; Lakshmanan et al, 2018). It is noteworthy that mitochondrial dysfunction in a particular tissue is able to induce stress responses in distal tissues through the mitochondrial unfolded protein response (Zhao et al, 2002; Durieux et al, 2011; Zhang et al, 2018) and other hormonal signaling pathways (Tyynismaa et al, 2010; Khan et al, 2017), suggesting potential organism-wide consequences of focal mitochondrial mutations.…”
Section: Genetic Sources Of Mitochondrial Heterogeneitymentioning
confidence: 99%
“…Over the course of an individual's lifespan, mtDNA mutations and deletions accumulate within cells and tissues; in some instances, mutant mtDNA propagates at an even faster rate than its wild-type counterparts (Trifunovic et al 2004;Lakshmanan et al 2018). It has been suggested that such age-related increases in mtDNA heteroplasmy may contribute to the onset and progression of various diseases (Cortopassi et al 1992;Chen et al 2011).…”
Section: Ddmdm To Quantify Common Mtdna Deletions: a Pilot Study In Cmentioning
confidence: 99%
“…MtDNA damage was assessed using Real Time-qPCR according to the published method. (Cristina et al, 2009;Lakshmanan et al, 2018) The pair of primers (Forward: GTTTATGCTGCTGTAGCGTG, Reverse: CTGTTAAAGCAAGTGGACGAG) were used to normalize the mitochondrial genome. The results were normalized to genomic DNA using primer pairs specific for ama-1(Forward: TGGAACTCTGGAGTCACACC, Reverse: CATCCTCCTTCATTGAACGG).…”
Section: Methodsmentioning
confidence: 99%